검은가슴할미새사촌(가칭: Pericrocotus tegimae) 국내 첫 월동 기록 - 은나현(Na-Hyeon Eun); 김은미(Eun-mi Kim); 강창완(Chang-wan Kang) (한국조류학회지, 2021)
2020년 12월 3일부터 31일까지 제주도 서귀포시에 위치한 계곡 인근에서 검은가슴할미새사촌이 관찰되었고 최대 4개체가 한 달 정도 동일한 장소에서 관찰되어 월동이 확인되었다. 이전에 국내에서 관찰기록은 있으나 미보고된 종으로 검은가슴할미새사촌의 첫 월동 사례를 보고하고자 한다. From December 3 to 31, 2020, Ryukyu Minivet(Pericrocotus tegimae) were observed near a valley in Seogwipo, Jeju Island, and up to four individuals were observed in the same place for a month, confirming wintering. This observation is first wintering record of Ryukyu Minivet(Pericrocotus tegimae) that have observation records but have not been reported in Republic of Korea. KCI Citation Count: 1